Facilitating reading engagement by foregrounding students’ voices through epistolary writing: a case study - Puteri Rohani Megat Abdul Rahim,; Fatimah Hashim, (Penerbit UKM, 2015)
Engaging students in reading permits students to experience reading in a more meaningful manner as well as develop their identity as effective readers. Currently, the teaching of reading does not allow students to experience reading in an engaging and meaningful manner because the process of retrieving the required information at the end of the reading text has hindered them from experiencing reading in this manner. This exploratory study presents an approach to facilitate students‟ reading engagement through the employment of epistolary writing. The purpose was to explore the employment of epistolary writing in facilitating ESL students‟ reading engagement. The students wrote their understanding and interpretation of printed texts in the form of a letter to their instructor. Three third year students participated voluntarily in this case study. Data were collected through semi-structured interviews and documents such as students‟ letters, instructor's reflective notes, and pre-teaching and post-teaching questionnaires. Findings showed that the students appreciated that their voices were being considered throughout the teaching and learning process. They also described how relating their ideas through epistolary writing contributed to personal changes of viewing reading as an active process. The research highlights the value of including students‟ voices in the teaching and learning process. Allowing students to voice and share their learning experiences with their peers and the instructor, enabled the instructor to construct a better instructional approach to assist the students in their progress as engaged readers. In addition, this study extends knowledge that writing plays a key role in L2 tertiary level academic literacy development.